Access to fused π-extended acridone derivatives through a regioselective oxidative demethylation. Issue 32 (4th August 2021) - Ding, Weiwei; Zhang, Gang
Abstract : The oxidative demethylation of dimethoxyacridone with ceric ammonium nitrate gives an ortho -quinone regioselectively, which was used to synthesize π-extended acridone derivatives. Abstract : The oxidative demethylation of ortho -dimethoxyacridone with ceric ammonium nitrate (CAN) regioselectively furnished an ortho -quinone leaving a methoxyl group unreacted, which further condensed with aromatic ortho -diamines to afford angularly fused π-extended acridone derivatives. Crystallographic analysis reveals the distinct manner of molecular packing in the crystals according to the dimension of π-extension. The benzene at the turning point possesses a shorter outer bond and a longer inner bond, which affects molecular conjugation and results in weakened aromaticity.